Role of Health Care Professionals in Multidisciplinary Pain Treatment Facilities in Canada. (2008) - Peng, Philip; Stinson, Jennifer N; Choiniere, Manon; Dion, Dominique; Intrater, Howard; LeFort, Sandra; Lynch, Mary; Ong, May; Rashiq, Saifee; Tkachuk, Gregg; Veillette, Yves; the STOPPAIN Investigators Group,
Abstract : PURPOSE: To examine the role of health care professionals in multidisciplinary pain treatment facilities (MPTF) for the treatment of chronic pain across Canada. METHODS: MPTF were defined as clinics that advertised specialized multidisciplinary services for the diagnosis and management of chronic pain, and had staff from a minimum of three different health care disciplines (including at least one medical specialty) available and integrated within the facility. Administrative leaders at eligible MPTF were asked to complete a detailed questionnaire on their infrastructure as well as clinical, research, teaching and administrative activities. RESULTS: A total of 102 MPTF returned the questionnaires. General practitioners, anesthesiologists and physiatrists were the most common types of physicians integrated in the MPTF (56%, 51% and 32%, respectively). Physiotherapists, psychologists and nurses were the most common nonphysician professionals working within these MPTF (75%, 68% and 57%, respectively), but 33% to 56% of them were part-time staff. Only 77% of the MPTF held regular interdisciplinary meetings to discuss patient management, and 32% were staffed with either a psychologist or psychiatrist. The three most frequent services provided by physiotherapists were patient assessment, individual physiotherapy or exercise, and transcutaneous electrical nerve stimulation. The three most common services provided by psychologists were individual counselling, cognitive behavioural therapy and psychodynamic therapy. The major roles of nurses were patient assessment, assisting in interventional procedures and patient education. CONCLUSION: Different health care professionals play a variety of important roles in MPTF in Canada. However, few of them are involved on a full-time basis and the extent to which pain is assessed and treated in a truly multidisciplinary manner is questionable.